2020
DOI: 10.1155/2020/4835653
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy as a Salvage Therapy after Incomplete Radiofrequency Ablation for Hepatocellular Carcinoma: A Retrospective Cohort Study

Abstract: Residual tumor tissue after radiofrequency ablation (RFA) is inevitable in clinical practice, and the optimal management of residual tumor after RFA has not been established. To evaluate the efficiency and toxicity of stereotactic body radiotherapy (SBRT) as a salvage therapy after incomplete RFA for hepatocellular carcinoma (HCC), we retrospectively included 32 HCC patients with an initial incomplete response (iIR) to RFA from May 2011 to August 2018. An iIR was defined as the presence of residual enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, the efficacy of TACE + SBRT was comparable to the previously reported local control rate of 88% following the combination of TACE + RFA [ 12 ]. In addition, Fu et al reported the efficacy of SBRT as a salvage therapy after the incomplete RFA [ 13 ]. Recently, Bettinger et al reported that the therapeutic effect of radiotherapy was comparable to that of sorafenib [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the efficacy of TACE + SBRT was comparable to the previously reported local control rate of 88% following the combination of TACE + RFA [ 12 ]. In addition, Fu et al reported the efficacy of SBRT as a salvage therapy after the incomplete RFA [ 13 ]. Recently, Bettinger et al reported that the therapeutic effect of radiotherapy was comparable to that of sorafenib [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other conditions included lesions adjacent to main portal or hepatic vein (three cases), located close to the heart (two cases), and had poor conspicuity in US and contrast-enhanced ultrasound images (one case). As the risk for insu cient ablation and di cult operation are predictable, we directly planned SBRT as the foremost treatment for these lesions, other than previously using SBRT as a salvage therapy after incomplete RFA performance [18,20], which yielded a 1-3 years' local control rate of 81.8-86.6% and OS rate of 85.4-85.6%. Comparatively, our therapy achieved a much better treatment effect with a high 1-year local control rate (97.4%), a promising prognosis with an acceptable 1-year PFS (80%), and a higher OS rate (100% and 89.9% for 1 and 2 years, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by the previously successful combined application of RFA and SBRT in HCC patients in a relative early stage [18,19], and the requirement for an effective treatment strategy for early multifocal HCCs, especially those ineligible or unavailable for RFA performance, we propose a novel treatment strategy combining SBRT and RFA for different HCC lesions coexisting in the same patient. We performed a retrospective single-arm study by applying RFA and SBRT treatment in 39 multifocal HCC lesions from 15 patients in BCLC stage A4-B1, evaluating the bene t to prognosis and possible adverse effect during follow-up, then determining their comprehensive therapeutic consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RFA and subsequent SBRT treatment included multifocal lesions treated with RFA and SBRT separately, and local/distant recurrent lesions after RFA treatment were treated with SBRT. For the latter case, a few studies exhibited the feasibility of using SBRT on residual RFA-treated lesions with encouraging outcomes [6,7]. Regrettably, however, there are no data available on the conditions of the short-term application of RFA and SBRT in the same patient for multifocal lesions or intrahepatic distant recurrence, which is very common in the progress of HCC.…”
Section: Introductionmentioning
confidence: 99%